The impact of electricity shortages on large- and medium-scale manufacturing industries in Ethiopia - Woldesenbet, Almaz Bekele (Energy Research Centre, 2014)
This study examines the impact of electricity shortages on the Large- and Medium-Scale Manufacturing Industry (LMSMI) in Ethiopia, using data obtained from a case study of 16 LMSMI firms that was undertaken in Addis Ababa from January 2004 to February 2004. In addition, the study examines the causes of these electricity shortages. Ethiopia's electricity supply relies very heavily on hydroelectric power, with geothermal, natural gas, solar, coal and diesel together providing only 1% of the total electricity supply. Significant power shortages occurred in the years 1995/96, 1997/98 and 1999/2000, with a particularly severe power shortage happening in 2002/03. The causes of these included a general increase in electriCity demand, without a corresponding increase in installed hydropower capacity, and a sustained period of drought. The case study findings showed that power outages were particularly costly in the LMSMI sector, through production and raw materials losses, damage to equipment, and the additional investment and operating costs of self-generation among those firms that purchased and used their own diesel generators as a backup source of electriCity. The case study results indicated that power outages caused firms without backup generators to lose approximately 15% to 30% of their potential production in 2002/03. Even in the other years when the power shortages were less severe, losses could reach up to 10%. By extrapolating the sampled firms' production losses to the total number of LMSMI firms in the country, it can be estimated that the country may have lost 10% to 15% of total yearly gross value of production that could have contributed from this sector and 1 % to 3% of total yearly government revenue. In the past, because of the low level of development in the Ethiopian LMSMI sector, the costs of power outages on this sector had not been as big, despite their high frequency. It is envisaged that, when the country's economy grows and the government's new policy (the Agricultural Development-Led Industrialization strategic plan) increases the economy's dependence on LMSMI production, then power outages would certainly have a much greater impact on the LMSMI sector as well as on the total economy of the country. In order to avoid this, therefore, some of the constraints which contributed to power shortages in the past (such as poor planning and governance, bad decision-making, and a lack of integrated planning), should be addressed. In addition, unplanned power outages, which, according to the firms interviewed, had an even greater impact than scheduled power outages, should be minimized. Hopefully, in the future, these measures will improve the performance and reliability of the electriCity supply in the country.